2022
DOI: 10.3390/agronomy12092020
|View full text |Cite
|
Sign up to set email alerts
|

Two Allelopathic Substances from Plumbago rosea Stem Extracts and Their Allelopathic Effects

Abstract: The plant Plumbago rosea Linn., belonging to the Plumbaginaceae family, is an important medicinal herb distributed in part of Southeast Asia, and there are many reports of its pharmacological properties. However, the allelopathic activities of P. rosea have not been examined. Thus, the present study was conducted to assess the allelopathic activity of P. rosea and to identify its allelopathic substances. The aqueous methanol stem extract of P. rosea significantly suppressed the seedling growth of barnyard gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Additionally, the I 50 values of the shoot and root growth of the four test plants varied, showing that the inhibition by the M. tenacissima extracts was species dependent (Table 1). A similar trend in concentration and species-dependent inhibitory activity for extracts of Elaeocarpus floribundus, Anredera cordifolia, Garcinia xanthochymus, and Plumbago rosea have also been reported [39][40][41][42]. Therefore, the M. tenacissima leaf extracts may contain allelopathic substances responsible for the growth-inhibitory activities against the four tested plants.…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, the I 50 values of the shoot and root growth of the four test plants varied, showing that the inhibition by the M. tenacissima extracts was species dependent (Table 1). A similar trend in concentration and species-dependent inhibitory activity for extracts of Elaeocarpus floribundus, Anredera cordifolia, Garcinia xanthochymus, and Plumbago rosea have also been reported [39][40][41][42]. Therefore, the M. tenacissima leaf extracts may contain allelopathic substances responsible for the growth-inhibitory activities against the four tested plants.…”
Section: Discussionsupporting
confidence: 67%
“…The species- and concentration-dependent inhibitory effects are also consistent with many research findings on different plant extracts of Leucas cephalotes (Roth) Spreng [ 51 ], Annona muricana (L.) [ 52 ], Senna garrettiana [ 53 ], Dregea volubilis (L.f.) [ 29 ], Elaeocarpus floribundus Blume [ 30 ], Marsdenia tenacissima (Roxb.) Moon [ 31 ], and Plumbago rosea [ 32 ]. In addition, the I 50 values revealed that the roots of the four tested plants were more susceptible to extracts of P. chinense than the hypocotyls/ coleoptiles.…”
Section: Discussionmentioning
confidence: 99%
“…Several have researchers also documented that the root and hypocotyl growth of L. sativum is significantly suppressed by loliolide, cis-3-hydroxy- α -ionone, and (3R)-3-hydroxy- β -ionone isolated from Elaeocarpus floribundus Blume [ 30 ]; a novel compound of steroidal glycoside 1 and common compound steroidal glycoside 2, isolated from Marsdenia tenacissima (Roxb.) Moon leaves extracts [ 31 ]; 7,4′,5′-tri- O -methylampelopsin and 7,4′,5′-tri- O -methyl dihydroquercetin isolated from Plumbago rosea [ 32 ]; a novel compound of garcienone, isolated from Garcinia xanthochymus Hook [ 33 ]. In addition, four characterized allelochemicals of (−)-catechin, (−)-epicatechin, resveratroloside, and piceatannol glucoside were extracted from Polygonum cuspidatum Sieb.…”
Section: Introductionmentioning
confidence: 99%